(untitled) (Marketing Journal, 2025)
In the context of the digital transformation of the economy, financial literacy issues are becoming particularly important. A lack of knowledge in the field of personal finance management, investment, and digital financial instruments can lead to financial risks and a decrease in the economic stability of the population. The article examines opportunities and ways to increase financial literacy in the context of the digital economy. Recently, the issue of raising the level of education among the people has become the main priority for the development of Uzbekistan, which justifies the relevance of the chosen research topic.